Professional training of future teachers in higher education for sustainable development in Germany - Naletskaya, Natalia N. (Journal of the Belarusian State University. Ecology, 2018)
The article presents the special aspects and approaches of the university training of future teachers in Germany, moreover proposed steps to improve their training in modern conditions. Analysis of the scientific literature allows to assert that the system of higher education in Germany differs in structure and content of education. In turn, it affects the improvement of quality of the teacher's work and the educational level of young people. The presented experience will be useful for many educational institutions of the Republic of Belarus.
Keywords: educational policy in Germany; system of higher education; training of future teachers; ecological education for sustainable development